One-pot synthesis of ternary-emission molecularly imprinted fluorescence sensor based on metal–organic framework for visual detection of chloramphenicol. (15th February 2023) - Wu, Xiaodan; Tang, Sisi; Zhao, Pengfei; Tang, Kangling; Chen, Yu; Fu, Jinli; Zhou, Shu; Yang, ZhaoXia; Zhang, Zhaohui
Highlights: A ternary-emission fluorescence imprinted sensor was synthesized by one-pot method. The imprinted sensor offered rich color variations for visual detection of chloramphenicol in food. The imprinted sensor possessed rapid response, high selectivity and sensitivity, wide linear range for detection CAP. NH2 -UiO-66 improved the fluorescence response sensitivity and response speed. Abstract: In this paper, a ternary-emission fluorescence imprinted polymer was one-pot synthesized by sol–gel method after mixing luminescence metal organic framework, green CdTe and near infrared red CdTe for visual detection of chloramphenicol in food. The ternary-emission fluorescence imprinted sensor showed wider linear range within concentration of 10 pM–0.5 nM and 0.5 nM–4.5 nM, with rapid response time of 3 min and the lower detection limit of 3.8 pM toward chloramphenicol. Meanwhile, NH2 -UiO-66 improved the fluorescence sensitivity and response speed, the near-infrared CdTe enhanced the anti-interference ability of the imprinted sensor. Compared with the traditional single-emission and dual-emission fluorescence imprinted sensors, the ternary-emission imprinted sensor provided richer color changes from yellowish green to apricot to orange-salmon to amaranth to purple to final blue. It was applied to detect trace chloramphenicol in food with the recoveries of 98.2–101.2 %, which provided a new way for rapid visual detection of chloramphenicol.